Annual mass-balance time series of Dongkemadi Glacier, 2000–20, from a linear albedo-based model using geodetic data and validated with the glaciological method - Lin Liu; Zhimin Zhang; Yongling Sun; Xuguo Shi; Liming Jiang (Journal of Glaciology)
Long-term time series of annual glacier mass balance is important for revealing a glacier's response to regional climate variations. However, for the Tibetan Plateau, time series of annual glacier mass balance with more than 10 consecutive years remains scarce due to the inaccessibility and harsh climate conditions. In this study, we established an albedo-based model to reconstruct annual glacier mass balance for 2000–20 over the Dongkemadi Glacier, based on multitemporal geodetic estimates and annual minimum glacier-wide mean surface albedos. Geodetic glacier mass-balance estimates for 2000–12, 2012–14 and 2014–18 were obtained by comparing glacier surface topographic data. Minimum surface albedos were obtained from the moderate-resolution imaging spectroradiometer daily snow albedo products for 2000–20. The estimated results are supported by the field measurements of annual glacier mass balance. During the early 2000s, we detected a relatively balanced state of glacier mass change, whereas a pronounced mass loss of more than −0.5 m w.e. was found for most years in the 2010s. By analyzing the regional climate variations with the ERA5-Land monthly averaged data, we found that the accelerated glacier mass loss can be attributed to both decreased annual snowfall and increased summer air temperature.